Expanding Remote Embedded Systems Education: Integrating the MICRO Remote Lab Across Courses and Curricula - Czekansky, Jakob; Sauer, Justin; Sen, Onur Melik; Volkening, Maurice (International Journal of Advanced Corporate Learning (iJAC), 2026)
Practical training in embedded systems often suffers from resource shortages, scheduling restrictions, and limited accessibility. This article introduces MICRO, a web-based remote laboratory at University of Applied Sciences Mittelhessen (THM) that enables real-time access to microcontroller and FPGA hardware via standardized and scalable Cubes and Assemblies, replacing error-prone home construction kits with robust setups. MICRO is used extensively in teaching and anchored in the curriculum: from register-oriented programming in the Microprocessor Technology module to FPGA-based logic design in Digital Technology, to IoT-oriented rapid prototyping in Technical Computer Science II, and to the interdisciplinary Computer Science Project connecting the second and third semester, where students design and implement full-stack applications that integrate web technologies, databases, and remotely provided embedded hardware, thereby creating a consistent learning path across levels of abstraction. The article consolidates the curricular anchoring of MICRO across multiple modules, the underlying architecture and technical innovations for scalability and collaboration, and lessons learned together with an outlook on formal effectiveness studies, open-source release, and data-driven assessments.